ENGLISH-APPRAISAL OF ISLAMIC DEMOCRATIZATION IN ZIA UL-HAQ REGIME - Muhammad Ibrahim; Razia Musarrat (دی اسکالر)
Pakistan established on ideological basis. The core objective is to run the state on the principle of Islam. Islam as religion stresses on the consultancy to govern Muslim state. From the beginning of Islam, all the caliphs adopted the process of advisory council which led to democratization in those periods. There is hot debate on the democratic system in Pakistan. The majority of people wished the Islamic governing system. There is serious and hot discussion with different references in the history of Pakistan. There are different views on the lslamization policy of General Zia-ul-Haq. Political decisions were made to democratize the society on Islamic principles. There were different merits and demerits of the regime in Pakistan. The prime objective of study is to focus the Islamic democratization in Zia-ul-Haq regime.  The descriptive and analytical method is adopted for the study.